Fluid-based biomarkers in neurodegeneration: current findings and future directions - Blagojević, Sanja; Jeremić, Marija; Marković, Ivanka (Medicinski podmladak, 2024)
With the increase in life expectancy, the prevalence of neurodegenerative disorders is expected to rise in many countries of the world. The need for reliable biomarkers in neurodegenerative diseases is crucial to improving timely and accurate clinical diagnostics, facilitating the development of disease-modifying therapies, and monitoring patient progress. Complex pathology of neurodegenerative diseases can, in many cases, be reflected in the extracellular fluid, allowing for the development of soluble biomarkers that can mirror neuropathology in the cerebrospinal fluid or blood. This review showcases an overview of the current findings, latest developments in the field, as well as applications of fluid based biomarkers in neurodegenerative diseases.
Keywords: biomarkers; neurodegeneration; CSF; blood